2021
DOI: 10.1139/cjpp-2021-0260
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac hypertrophy caused by hyperthyroidism in rats: the role of ATF-6 and TRPC1 channels

Abstract: Hyperthyroidism influences the development of cardiac hypertrophy. Transient receptor potential canonical channels (TRPCs) and ER stress are regarded as critical pathways in cardiac hypertrophy.Hence, we aimed to identify the TRPCs associated with ER stress in hyperthyroidism-induced cardiac hypertrophy.20 adult Wistar albino male rats were used in the study.The control group was fed with standard food and tap water. The group with hyperthyroidism was also fed with standard rat food, along with tap water that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…41 The deterioration of Ca 2+ ion balance induced by ATF6, IRE1 and PERK leads to myocardial hypertrophy caused by hyperthyroidism. 43 At the same time, the nucleotide-binding domain of GRP78 dissociates from the lumen domain of IRE1 and PERK, leading to further activation of UPR. 44 As ER stress becomes chronic or excessive, it may induce the proapoptotic transcription factor CHOP, which may lead to apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…41 The deterioration of Ca 2+ ion balance induced by ATF6, IRE1 and PERK leads to myocardial hypertrophy caused by hyperthyroidism. 43 At the same time, the nucleotide-binding domain of GRP78 dissociates from the lumen domain of IRE1 and PERK, leading to further activation of UPR. 44 As ER stress becomes chronic or excessive, it may induce the proapoptotic transcription factor CHOP, which may lead to apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that the activation of ATF6 and IRE1α can directly upregulate the transcription or processing of mRNA of UPR genes, 41,42 while PERK inhibits the activation of ER and reduces the protein load of ER 41 . The deterioration of Ca 2+ ion balance induced by ATF6, IRE1 and PERK leads to myocardial hypertrophy caused by hyperthyroidism 43 . At the same time, the nucleotide‐binding domain of GRP78 dissociates from the lumen domain of IRE1 and PERK, leading to further activation of UPR 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Frontiers in Pharmacology frontiersin.org 10 initiation and decreases the protein load on the ER (Lee et al, 2002). ATF-6, IRE1 and PERK-induced deterioration of the Ca 2+ ion balance leads to cardiac hypertrophy caused by hyperthyroidism (Bektur Aykanat et al, 2021), and PERK was also essential during the experiments for avoiding TAC-induced congestive HF (Liu et al, 2014). In line with these findings, we found that there was a remarkable change in the activation of IRE1, PERK and ATF-6 in Ang II-treated CMs and CFs, suggesting that the ER stress induced by Ang II participated in cardiomyocyte hypertrophy and fibroblast activation.…”
Section: Figurementioning
confidence: 99%
“…In contrast, myocardial fibrosis is a key factor affecting the progression of HTC. THs induce endoplasmic reticulum stress (ERS) [ 6 ] and apoptosis in cardiomyocytes [ 7 ] while increasing the force and speed of myocardial contraction [ 8 ] and the burden on the heart. Thus, it can lead to cardiac hypertrophy and left ventricular dysfunction [ 9 ], resulting in heart failure [ 10 , 11 ] and dilated cardiomyopathy [ 12 ].…”
Section: Introductionmentioning
confidence: 99%